Systemic delivery of a mitochondria targeted antioxidant partially preserves limb muscle mass and grip strength in response to androgen deprivation. (15th September 2021) - Rossetti, Michael L.; Dunlap, Kirsten R.; Salazar, Gloria; Hickner, Robert C.; Kim, Jeong-Su; Chase, Bryant P.; Miller, Benjamin F.; Gordon, Bradley S.
Abstract: Muscle mass is important for health. Decreased testicular androgen production (hypogonadism) contributes to the loss of muscle mass, with loss of limb muscle being particularly debilitating. Androgen replacement is the only pharmacological treatment, which may not be feasible for everyone. Prior work showed that markers of reactive oxygen species and markers of mitochondrial degradation pathways were higher in the limb muscle following castration. Therefore, we tested whether an antioxidant preserved limb muscle mass in male mice subjected to a castration surgery. Subsets of castrated mice were treated with resveratrol (a general antioxidant) or MitoQ (a mitochondria targeted antioxidant). Relative to the non-castrated control mice, lean mass, limb muscle mass, and grip strength were partially preserved only in castrated mice treated with MitoQ. Independent of treatment, markers of mitochondrial degradation pathways remained elevated in all castrated mice. Therefore, a mitochondrial targeted antioxidant may partially preserve limb muscle mass in response to hypogonadism. HIGHLIGHTS: Markers of increased ROS were previously seen in limb muscle following castration. Markers of mitochondrial degradation pathways were higher following castration. These were inversely were related to limb muscle mass following castration. The antioxidant, MitoQ, partially preserved limb muscle mass following castration. Increased markers of mitochondrial degradation pathways were unaffected by MitoQ.